ANALISIS PENERAPAN MEDIA DIGITAL FLIPBOOK TERHADAP PENINGKATAN MOTIVASI BELAJAR BAHASA JAWA PESERTA DIDIK KELAS IV SDN GONDORIYO SEMARANG - Asyifa, Naufal Faza; Samtiadji, Prima; Aulia , Aida Salsabila; Salsabila, Arina Nur; Sarnita; Ismunadi, Ali (Universitas Islam Raden Rahmat Malang, 2025)
This study aims to determine the effectiveness of digital media Flipbook in increasing the motivation to learn Javanese language in class IV students of SDN Gondoriyo, Semarang. The background of the study is the low motivation of students to learn due to the dominance of the lecture method and the lack of learning media innovation. The research used quantitative methods with a pre-experimental one group pretest-posttest design. Data were collected through a learning motivation questionnaire that had been tested for validity and reliability. The results showed that all questionnaire items were valid (r count > r table) and reliable (Cronbach's Alpha = 0.892). The data were normally distributed (significance > 0.05), so the analysis continued with paired sample t-test and N-Gain test. The t-test results showed a significant difference between the pretest and posttest (p < 0.001), while the N-Gain of 0.65 showed a fairly effective category. Based on the results of the study, the use of Flipbook is effective enough to increase the motivation to learn Javanese Language for Grade IV Students of SDN Gondoriyo. Keywords: Javanese language, digital media, elementary school, Flipbook, learning motivation